Students’ Perceptions of the Virtual Reality (VR) Environment through GeoVR-Xplorer at Kelantan Matriculation College - Abdullah, Zuhaizi; Ayub, Siti Fadhilah; Hamzah, Nur Zarifah Syazana; Saifullah, Siti Sarah; Rahim, Noor Shuhada (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
The use of Virtual Reality (VR) technology in education is a new approach introduced to address the challenges of the Fourth Industrial Revolution (4IR). VR provides a realistic learning environment by employing an exploratory approach, particularly for science students studying chemistry. Molecular Geometry is one of the topics that requires a high level of imagination to understand the shapes of molecular compounds. Students' difficulties in visualizing these molecular structures in three dimensions (3D) have led researchers to develop a teaching aid called GeoVR-Xplorer. This study aims to identify students’ perceptions of the VR learning environment through the use of GeoVR-Xplorer. This descriptive study involved 48 students from the Science Department in their second semester of the Four-Semester System (SES) Programme for the 2023/2024 academic session. A set of questionnaires was used in this study, comprising five dimensions: immersion, interaction, imagination, motivational strategy, and problem-solving ability. The findings indicate that students’ perceptions of the VR learning environment using GeoVR-Xplorer were at a very high level, with a mean score of 6.85. Correlation tests conducted in this study revealed a strong positive relationship between students’ perceptions and their understanding. It is hoped that the findings of this study will provide valuable insights for lecturers and educational institutions regarding students' perceptions of the VR learning environment, enabling the broader adoption of this medium in the future.
Keywords: Virtual Reality; Exploratory; Realistic; Molecular Geometry; 3D